2003
DOI: 10.1080/01926230390241828
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Aquaflor (Florfenicol, 50% Type A Medicated Article), Administered in Feed to Channel Catfish, Ictalurus punctatus

Abstract: Aquaflor, a feed premix containing the broad spectrum antibacterial agent florfenicol (50% w/w), is being developed for use to control enteric septicemia (ESC) in channel catfish Ictalurus punctatus caused by the gram-negative enterobacterium Edwardsiella ictaluri. The recommended dose of Aquaflor to control ESC is 10 mg/kg body weight (BW)/day for 10 days. The study objective was to determine the safety of Aquaflor administered in feed to channel catfish at doses of 0 (control), 10, 30, and 50 mg/kg BW/day fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 25 publications
2
26
0
Order By: Relevance
“…Herein, in our study, the spleen showed a reduction in lymphocytes and hemosiderin pigments comparing with other groups. The results coordinated with that reported by Gaikowski et al (2003) and Reda et al (2013).…”
Section: Discussionsupporting
confidence: 91%
“…Herein, in our study, the spleen showed a reduction in lymphocytes and hemosiderin pigments comparing with other groups. The results coordinated with that reported by Gaikowski et al (2003) and Reda et al (2013).…”
Section: Discussionsupporting
confidence: 91%
“…Florfenicol is a broad spectrum antibiotic used for the treatment of bacterial infections in mammals, birds, fish, and lobsters [1, 2, 4, 18, 19]. In this study, sTNF- α values were found to increase after LPS application ( P < 0.05) (Table 1).…”
Section: Commentmentioning
confidence: 53%
“…in fish [3]. It has been reported that florfenicol can be safely used at differing doses in tilapia fish and dose related mild decreases in the hematopoietic/lymphopoietic tissues have been observed with its use in channel catfish [4]. …”
Section: Introductionmentioning
confidence: 99%
“…Florfenicol (FF) is the most important antibiotic employed in the aquaculture . In some countries like Japan, South Korea, Norway, Chile, Canada, and United Kingdom, FF is an antimicrobial agent registered for the treatment of susceptible bacterial diseases in several fish species . In the case of the salmonid species, FF is used for the treatment and control of furunculosis caused by Aeromonas salmonicida .…”
Section: Introductionmentioning
confidence: 99%
“…In some countries like Japan, South Korea, Norway, Chile, Canada, and United Kingdom, FF is an antimicrobial agent registered for the treatment of susceptible bacterial diseases in several fish species . In the case of the salmonid species, FF is used for the treatment and control of furunculosis caused by Aeromonas salmonicida . Although medicated feed is commonly employed in salmon farming to prevent bacterial infections, drugs are not completely ingested or unmetabolized.…”
Section: Introductionmentioning
confidence: 99%